Can self-powered piezoelectric materials be used to treat disc degeneration by means of electrical stimulation? - Huang, Huagui; Wang, Kaizhong; Liu, Xianyan; Wang, Jinzuo; Suo, Moran; Liu, Xin; Li, Zhonghai (Frontiers in Bioengineering and Biotechnology, 2024)
Intervertebral disc degeneration (IDD) due to multiple causes is one of the major causes of low back pain (LBP). A variety of traditional treatments and biologic therapies are currently used to delay or even reverse IDD; however, these treatments still have some limitations. Finding safer and more effective treatments is urgent for LBP patients. With increasing reports it has been found that the intervertebral disc (IVD) can convert pressure loads from the spine into electrical stimulation in a variety of ways, and that this electrical stimulation is of great importance in modulating cell behavior, the immune microenvironment and promoting tissue repair. However, when intervertebral disc degeneration occurs, the normal structures within the IVD are destroyed. This eventually leads to a weakening or loss of self-powered. Currently various piezoelectric materials with unique crystal structures can mimic the piezoelectric effect of normal tissues. Based on this, tissue-engineered scaffolds prepared using piezoelectric materials have been widely used for regenerative repair of various types of tissues, however, there are no reports of their use for the treatment of IDD. For this reason, we propose to utilize tissue-engineered scaffolds prepared from piezoelectric biomaterials with excellent biocompatibility and self-powered properties to be implanted into degenerated IVD to help restore cell type and number, restore extracellular matrix, and modulate immune responses. It provides a feasible and novel therapeutic approach for the clinical treatment of IDD. In recent years, researchers have discovered 删除[Huagui Huang]: regulating 删除[Huagui Huang]: modulating immunity, and promoting tissue repair 删除[Huagui Huang]:As IDD progresses, the electrical generation capacity of IVD decreases significantly.